YUK NGAJI: DIGITALIZATION OF GENERATION Z’S RELIGIOUS ACTIVITIES ON INSTAGRAM ACCOUNT - Virga, Rika Lusri; Shovmayanti, Noor Afy; Yusoff, Rahmawati Mohd; Rosa, Naili (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2025)
Religious teachings are increasingly disseminated through digital media, particularly among Indonesia’s Generation Z, who actively engage with platforms like Instagram. However, existing studies primarily focus on the effectiveness of digital da’wah rather than how Gen Z interprets and internalizes religious content in these spaces. Addressing this gap, this study examines how Gen Z constructs meaning from digital da’wah through an ethnographic analysis of the Instagram accounts @yukngajipku and @yukngajijogja over a one-year period (January–December 2023), analyzing 297 and 369 posts, respectively. Findings reveal three key themes: the visualization of religious joy, where Islamic teachings are presented engagingly; volunteerism as a marker of religious observance, emphasizing activism as a faith-driven commitment; and the intimacy of the hijrah community, fostering a sense of belonging. Unlike previous studies focused on message dissemination, this research highlights the identity-shaping role of digital da’wah, demonstrating that Gen Z actively engages in religious meaning-making. The findings offer practical implications for digital da’wah practitioners, emphasizing the need for engaging, visually driven, and community-oriented content to sustain youth involvement. For religious educators, this study underscores the importance of incorporating interactive and relatable digital strategies to enhance religious learning. Policymakers can utilize these insights to develop media literacy initiatives that equip Gen Z with the critical thinking skills necessary to navigate digital religious content responsibly.